Associations of employment disruptions and financial hardship among individuals diagnosed with cancer in the United States. Issue 28 (1st October 2022) - Halpern, Michael T.; De Moor, Janet; Han, Xuesong; Zhao, Jingxuan; Zheng, Zhiyuan; Yabroff, K. Robin Robin
Abstract : 47 Background: Financial hardship is experienced by approximately half of working-age individuals diagnosed with cancer. Many working individuals diagnosed with cancer also experience disruptions with their employment. This study examines whether employment disruptions are associated with financial hardship among individuals diagnosed with cancer in the US. Methods: We utilized data from the 2016/2017 Medical Expenditure Panel Survey (MEPS) Experiences with Cancer self-administered questionnaires and identified individuals diagnosed with cancer at age >18 who worked for pay at the time of or following their cancer diagnosis. Employment disruption was defined as taking extended paid time off work; switching to a part time or less demanding job or to a flexible work schedule; and/or retiring early due to cancer, cancer treatment, or late effects. Financial hardship was defined in 3 domains: material (borrowing money, financial sacrifices, or being unable to cover medical costs); psychological (worrying about medical bills, financial stability, keeping job/income, or future earnings); and behavioral (delaying/forgoing medical care because of cost). Multivariable logistic regression analyses adjusting for the MEPS survey design were used to determine associations of employment disruption due to cancer with any financial hardship and with financial hardship intensity while controlling for patient demographic, health insurance, and clinical characteristics. Results: Among 732 individuals with a cancer history, 47.4% experienced employment disruptions and 55.9% experienced any financial hardship. Financial hardship was significantly more common among cancer survivors with employment disruption than without disruptions (68.7% vs. 44.5%; p-value of difference < 0.0001). Findings were consistent across multiple hardship measures and domains. Cancer survivors with employment disruptions were more likely to have greater (OR = 2.8; 95% CI 2.0, 3.9) financial hardship intensity. Individuals of race/ethnicity other than non-Hispanic White were also more likely to experience financial hardship while older individuals, women, and those with college education or who were married were less likely to experience financial hardship. Conclusions: Employment disruptions are common and significantly associated with multiple types of financial hardship among cancer survivors. Employer workplace accommodation and other policies to minimize disruptions among individuals diagnosed with cancer may reduce financial hardship in this vulnerable population.